Captain Underpants and the preposterous plight of the purple potty people : the eighth epic novel - Pilkey, Dav, 1966- (New York : Scholastic, 2006)
George and Harold hypnotize their principal who, believing he is the superhero Captain Underpants, leads them to the lair of the nefarious Dr. Diaper. They must then defeat his evil robot henchmen.
850
Accelerated Reader AR
Keywords: School principals -- Juvenile fiction; Heroes -- Juvenile fiction; Humorous stories